2011
DOI: 10.1111/j.1439-0329.2011.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity testing of four Bursaphelenchus species on conifer seedlings under greenhouse conditions

Abstract: The pinewood nematode, Bursaphelenchus xylophilus (Steiner and Buhrer, J. Agric Res. 48, 1934, 949), Nickle (J. Nematol. 2, 1970, 375), is the causative agent of the pine wilt disease and causes serious damage to pine forests around the world. During a survey for the pinewood nematode, four other Bursaphelenchus species (Bursaphelenchus mucronatus, B. sexdentati, B. anamurius and B. vallesianus) were isolated from wilted pine trees in Turkey. To understand the effects of these Bursaphelenchus species on wiltin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…(Akbulut et al 2007b;Dayı & Akbulut 2012). No studies have been performed to determine differences in the pathogenic effects of the nematodes on pine seedlings between greenhouse and outdoor conditions in Turkey.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…(Akbulut et al 2007b;Dayı & Akbulut 2012). No studies have been performed to determine differences in the pathogenic effects of the nematodes on pine seedlings between greenhouse and outdoor conditions in Turkey.…”
mentioning
confidence: 94%
“…The inoculum density used for each seedling was approximately 1000±100 nematodes of all life stages in 0.5 ml of distilled water. The adjustment of desired inoculum concentration, the selection of inoculation point and inoculation processes were performed at the same way done previously by Dayı & Akbulut (2012). All inoculation procedures were repeated identically for both greenhouse and outdoor treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, involvement of a few other Bursaphelenchus species, for example B. mucronatus and B. sexdentati, in PWD development remains unclear. However, recent controlled experimental inoculations in greenhouse conditions showed that these species also possess a pathogenic potential (Polomski & Rigling, 2010;Dayi & Akbulut, 2012). Therefore, because of the detection of B. xylophilus in Europe, strategic programmes have been applied to monitor the distribution of Bursaphelenchus spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent bioassays showed that experimental inoculation of 3-yearold P. sylvestris trees led to similar, if not identical, external and internal symptoms that are caused by B. xylophilus (Polomski & Rigling, 2010). More recently, a pathogenic potential of B. vallesianus was also observed in greenhouse conditions, where 2-year-old seedlings of three different pine species, Pinus nigra, P. brutia and P. pinea, were experimentally inoculated (Dayi & Akbulut, 2012). These findings supported the theory that overall mechanisms causing PWD are shared by all pathogenic Bursaphelenchus species, including B. vallesianus (Polomski & Rigling, 2010).…”
Section: Introductionmentioning
confidence: 99%